De la subalternidad del Trabajo Social y la dualidad teoría-práctica (como fuente de todos los males): On the subalternity of social work and the duality of theory and practice (as the source of all evils) - Ortega-Senet, Maria Belen; H. Caria, Telmo (Critical Proposals in Social Work, 2022)
Both the research that gives rise to this discussion and other studies conducted in Social Work, reveal that there remains a theoretical and practical disconnect in professional performance. In this article, which is shown as a hybrid between research and discussion document, this disconnection is problematized as the origin of the subalternity of the profession, articulating them with serious consequences such as: the neoliberal instrumentalization of the profession, the de-politicization of the discipline and the De-ligitimation of social work of Social Work as a source of knowledge. Based on concrete research with social workers at ESCNNA, we put forward some of the problematic hypotheses of the relationship between theory and practice in Social Work in general and in the work of protecting and guaranteeing rights with children in particular. One of the fundamental theses of the argument revolves around how these two dimensions are constructed in two separate dualities as distinct worlds, and how this disassociation places us, comparatively, at a disadvantage in terms of enunciating our own proposals for action. To conclude the discussion, we propose an exit door that leads us to an encounter between both lines, theory and practice, from critical self-observation. In this way, it offers itself as an alternative to the critical and complex systematization of experiences, as a way of finding points of inflection, questioning and individual and collective consciousness, from which to construct situated and also grounded, polyphonic and transforming proposals.